A towering task : the story of the Peace Corps [videorecording (DVD)] - Kelly, Shana; Bening, Annette; Carter, Jimmy, 1924-; Johnson-Sirleaf, Ellen, 1938-; Coyne, John; Cobbs, Elizabeth (First Run Features, 2023)
In 1961, President John F. Kennedy gave Americans a new way to serve their country: the Peace Corps. In its 60-year history, 200,000+ volunteers have traveled to more than 140 countries to carry out the organization's mission of world peace and friendship a towering task, indeed. Through interviews with Corps volunteers, Heads-of-State, scholars, journalists, and host country nationals, the film explores how this uniquely American government agency has attempted to answer Kennedy's call: "My fellow citizens of the world, ask not what America will do for you, but what together we can do for the freedom of man."